SOPHISTIC EDUCATION AS A SPIRITUAL MADRASAH FOR EARLY CHILDREN - Taja, Nadri; Baehaqi, Riyandi; Kunaepi, Widya Maratus Sholihah; Jannah, Revi Rusdatul (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
The goal of national education mandates three important messages from other messages namely faith, piety and noble character. The mandate of Law No. 20 of 2003 needs to be implemented in an activity called education. Education that is oriented towards the three components of this goal tends to be oriented towards the realm of Sufism as its embodiment. Therefore, this study examines how the construction of Sufistic education is focused on early childhood. Remembering that educating children is like carving on stone, it will be very easily imprinted in their soul. This qualitative research uses the literature study method to describe data that is interpreted from the ideas of Sufism related to children's education to be contextualized in building a style of Sufistic education. As part of the research, content analysis techniques were carried out in interpreting the finding data. The results of this study indicate that the concept of tazkiyatun nafs functions as a spiritual madrasah (ribath) by training one's soul through mujahadah and riyadhah so that the soul is clean. The implication of Sufistic education for early childhood is that a child is expected to know (ma'rifah) and love (mahabbah) only to God.